2013
DOI: 10.1177/0886260512469108
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence and the Place of Fear in Mother/Baby Relationships

Abstract: It should come as no surprise that when women who have raised babies in domestic violence come together to discuss the formation of relationships with their babies they raise issues of fear. Yet in current attachment studies about the formation of relationships between women and their babies, knowledge of fear based in lived experiences is undervalued. This article draws on a qualitative study of such experiences to explore ways in which fear impacted on 16 women and their babies. From this study it is discern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Previous research has shown that fear impacts on how mothers protect their children in violence (Buchanan et al, ). These fears have a rational basis, for example, it is well established that when women attempt to leave violent partners, their risk of violence and even death increases markedly (Mahoney, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that fear impacts on how mothers protect their children in violence (Buchanan et al, ). These fears have a rational basis, for example, it is well established that when women attempt to leave violent partners, their risk of violence and even death increases markedly (Mahoney, ).…”
Section: Resultsmentioning
confidence: 99%
“…Research with mothers has demonstrated that maternal protectiveness can include women separating children from the violence, trying to calm the partner and using reassuring strategies such as expressing love (Haight et al, ); women trying to respond to children's emotional needs after witnessing violence and trying not to leave children alone with partners (Lapierre, ); and women trying to create a violence‐free reality for their children (Peled and Gil, ). A recent Australian study further showed that women often think, feel and act protectively in a constant process of subtle, planned strategies (Buchanan et al, ). Research with children has found that young people either blame their mothers or feel that they developed a close relationship with their mothers because of the violence (McGee, ).…”
Section: Understanding Maternal Protectivenessmentioning
confidence: 99%
“…This included keeping the children away from violent acts, physically protecting children and appeasing partners so that they were not violent in front of the children. Buchanan et al.’s (2013) study of 16 mother–infant relationships similarly found that while enduring domestic violence women protected in many ways not generally recognised as protective and further, found that thinking protectively was a constant process. Research with former children raised in domestic violence has focussed on how they perceive the relationship between themselves and their mothers.…”
Section: Research Into Mother–child Relationships In Domestic Violencementioning
confidence: 99%
“…Over the past decade we have conducted in-depth face to face interviews and conducted focus groups with women who have survived domestic violence in six separate studies (Buchanan et al, 2013(Buchanan et al, , 2014(Buchanan et al, , 2015Wendt andZannettino, 2009, 2015;. Recently, we found ourselves engaging in conversations with each other about our experiences as interviewers.…”
Section: Methodology and Reflectionsmentioning
confidence: 99%